THE CORRELATION BETWEEN STUDENTS' LEVEL OF ANXIETY AND STUDENTS' ACHIEVEMENT IN WRITING CLASS - Heny Hartono (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2012)
Writing is one of the language skills which shows how a second language learner performs his or her verbal competence. Writing performance of an English learner can reflect the learner’s knowledge in English language patterns through the written discourse they present. However, due to several factors, writing in the target language is not always easy for a second language learner. Thus, there are some Indonesian students fail to perform their best in writing though those who can not achieve good mark in writing are not always the left behind students.Second language learner’s verbal performance is determined by three internal factors namely filter, organizer, and monitor (Dulay, Burt, Krashen, 1982:45-60). The first factor is a subconscious process  related to learner’s affective state which includes anxiety. This research starts from a hypothesis that students’ high level of anxiety is followed by lower students’ achievement. Thus, this research is aimed to prove the hypothesis as well as seeing if there is a strong correlation between the students’  level of anxiety and their achievement. The data were gained through document, questionnaire using Westide Test Anxiety Scale and Focus Group Discussion. The results of the study indicate a weak negative correlation between students’ level of anxiety and students’ achievement. From the result of the Focus Group Discussion,  it was found that the sources of students’ anxiety were varied.